Co-opted directors, covenant intensity, and covenant violations - Lim, Jesslyn; Do, Viet; Vu, Tram (Journal of Corporate Finance, 2020)
This study investigates how the level of board co-option might affect a borrowing firm's ex ante covenant intensity and ex post covenant violations. As the fraction of co-opted directors (those who joined the board after the CEO assumed office) increases, creditors include more covenant restrictions in their loan contracts, indicating that more co-opted boards are considered as weaker monitors. The results remain robust to various approaches accounting for endogeneity, and are not driven by alternative explanations such as CEO tenure, director inexperience, or CEO's involvement in the nominating committee. Ex post tests reveal that firms with more co-opted boards are more likely to violate loan covenants after controlling for covenant intensity. Non-co-opted independent directors appear to be the most effective monitors in mitigating covenant violations among revolving loans and loans to unrated borrowers.